2007
DOI: 10.1111/j.1524-4725.2007.33261.x
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Pathologic Effects on the Vein Wall of Foam Sclerotherapy

Abstract: In this in vivo report we analyze the capacity of 3% STD foam sclerotherapy to damage the saphenous vein wall. The damage is extremely fast and shows the detachment of the intimal and the development of the microthrombus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 9 publications
0
30
1
1
Order By: Relevance
“…One pathological study in vivo showed that a sclerosant in a foam vehicle completely destroyed the intimal barrier after 2-min exposure, leading to endothelial edema, exfoliation from the tunica media, and thrombogenesis in the tunica media over 30 min [14]. Polidocanol is a relatively weak sclerosant compared with conventional liquid sclerosants, such as ethanol or EO [15], but foam formulations have the same immediate pathological effect on the endothelium as liquid sclerosants.…”
Section: Discussionmentioning
confidence: 99%
“…One pathological study in vivo showed that a sclerosant in a foam vehicle completely destroyed the intimal barrier after 2-min exposure, leading to endothelial edema, exfoliation from the tunica media, and thrombogenesis in the tunica media over 30 min [14]. Polidocanol is a relatively weak sclerosant compared with conventional liquid sclerosants, such as ethanol or EO [15], but foam formulations have the same immediate pathological effect on the endothelium as liquid sclerosants.…”
Section: Discussionmentioning
confidence: 99%
“…The mean number of punctures required per patient was 3.96 (3)(4)(5)(6)(7), the mean number of sessions was 1.4 (1-3) and the mean volume of foam per session was 8.5 mL (10-23 mL).…”
Section: Resultsmentioning
confidence: 99%
“…3 There are several studies of UGFS treatment for CVI reporting good clinical results and high rates of venous trunk occlusion assessed by vascular echography. 4,5 However, few publications have confirmed the clinical results obtained with UGFS using objective parameters, such as the hemodynamic variations provoked by the treatment.…”
mentioning
confidence: 99%
“…Considering the good results of the ClariVein, our concept of mechanochemical ablation seems to be correct [5][6][7]. The mechanism of action of the Phlebogriffe has a solid pathophysiological basis [8][9][10]. The authors believe that the results of this pilot study will encourage further trials aimed at evaluation of this device.…”
Section: Discussionmentioning
confidence: 97%